NIEWYDOLNOŚĆ SERCA I PŁUC, TRANSPLANTOLOGIAGood long-term result of biventricular assisted circulation using POLCAS-RELIGA system in 16-year old boy with a irreversible heart failure – a case report - Pacholewicz, Jerzy; Hrapkowicz, Tomasz; Chodór, Beata; Kubacki, Krzysztof; Nadziakiewicz, Paweł; Borowicz, Marcin; Tylińska, Danuta; Sioła, Mirosława; Bauer, Anna; Jaworska, Izabela; Zakliczyński, Michał; Białkowski, Jacek; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
The long-term mechanical assisted circulation is a chance for the treatment of a selected group of patients in whom assisted circulation can lead to myocardial regeneration or as a bridge to transplantation. In this article we present the case of 16-yeare boy suffering heart failure due to ventricular non- compaction. Because of significant clinical worsening we decided to implant biventricular assisted circulation BIVAD using system POLCAS-RELIGA. During almost one year of BIVAD treatment the stabilization of hemodynamic parameters and reducing of pulmonary resistance has been observed. In the 358th day of assisted circulation heart transplantation with goof result has been performed